Type 1 interferon mediates chronic stress-induced neuroinflammation and behavioral deficits via complement component 3-dependent pathway - Tripathi, Ashutosh; Whitehead, Carl; Surrao, Katelyn; Pillai, Ananya; Madeshiya, Amit; Li, Yong; Khodadadi, Hesam; Ahmed, Anthony O; Turecki, Gustavo; Baban, Babak; Pillai, Anilkumar (Molecular psychiatry, 2021)
Chronic stress is a major risk factor in the pathophysiology of many neuropsychiatric disorders. Further, chronic stress conditions can promote neuroinflammation and inflammatory responses in both humans and animal models. Type I interferons (IFN-I) are critical mediators of the inflammatory response in the periphery and responsible for the altered mood and behavior. However, the underlying mechanisms are not well understood. In the present study, we investigated the role of IFN-I signaling in chronic stress-induced changes in neuroinflammation and behavior. Using the chronic restraint stress model, we found that chronic stress induces a significant increase in serum IFNβ levels in mice, and systemic blockade of IFN-I signaling attenuated chronic stress-induced infiltration of macrophages into prefrontal cortex and behavioral abnormalities. Furthermore, complement component 3 (C3) mediates systemic IFNβ-induced changes in neuroinflammation and behavior. Also, we found significant increases in the mRNA expression levels of IFN-I stimulated genes in the prefrontal cortex of depressed suicide subjects and significant correlation with C3 and inflammatory markers. Together, these findings from animal and human postmortem brain studies identify a crucial role of C3 in IFN-I-mediated changes in neuroinflammation and behavior under chronic stress conditions.